STRATEGIC MANAGEMENT IN TOURISM: HOW TO CREATE A COMPETITIVE ADVANTAGE OF TOURISM DESTINATIONS - Mašić, Branislav; Muhi, Bela; Nešić, Sandra; Jovanović, Dušan (Poslovna ekonomija, 2017)
In the conditions of globalization and acceleration of changes, tourism, as an economic activity and economic and social phenomenon, becomes increasingly important. State, territory, province, entity, regional, district, city to rural area tourism destinations need to strategically envisage and implement their competitive strategies in order to create a unique value proposition and competitive advantage. The competitive advantage of the tourist destination represents the system of tourist offer, marketing activities, organizational structure; creating a suitable environment and met expectations, which has a unique advantage over its competitors. In this sense, the subject of this paper is the application of strategic management from the standpoint of process and content in order for the tourist destinations to create and maintain competitive advantage. Investigation of the existing tourism development strategies in Serbia, Montenegro, Croatia and Republic of Srpska indicates a major problem of insufficient coordination and integration of unique tourism destination value proposition, at the regional, state level and their interconnectedness within clusters.